Surface Acoustic Wave Manipulation of Magnetic Skyrmions for Tunable Nanoscale Oscillators - Yang Yang; Chenye Zhang; Yahui Ji; Jinxing Zhang; Tianxiang Nan (Advanced Physics Research)
Abstract Magnetic skyrmions with unique topological spin textures, hold great promise for spintronic devices. In particular, the circular motion of skyrmions has shown potential as nanoscale oscillators for radio frequency applications. This study introduces a skyrmion‐based oscillator driven by surface acoustic waves (SAWs) through magnetoelastic coupling. Using micromagnetic simulations, precise tunability of the oscillator's frequency is demonstrated by varying the strain amplitude induced by a SAW and device dimensions. Furthermore, incorporating two skyrmions into the device significantly broadens the frequency tuning range. The proposed design offers a promising pathway for advancing nanoscale microwave frequency converters and spread spectrum modulation technologies.